2017
DOI: 10.1007/s11011-017-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of rice bran oil mitigate repeated haloperidol-induced tardive dyskinesia in male rats

Abstract: Tardive dyskinesia (TD) is associated with the use of antipsychotic drugs such as D2 antagonist haloperidol (HP). The chronic use of HP is involved in the causation of free radicals and/or oxidative stress. In view of the nootropic, anti-anxiety, anti-inflammatory-like effects of rice bran oil (RBO) in a variety of investigations, we assessed the protective properties of RBO on HP-induced TD and neurochemical alteration. Rats treated with HP orally at a dose of 0.2 mg/kg/day for a period of 5 weeks developed V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
11
1
1
Order By: Relevance
“…However, the exact pathophysiology of how this drug induces these side effects is not totally clear (Perera et al, 2011). Oxidative stress constitutes a potential pathogenic mechanism that may contribute to movement disturbances, especially to tardive dyskinesia (Perera et al, 2011; Wu et al, 2014; Samad and Haleem, 2017). Recent studies have shown that the repeated administration of haloperidol is able to induce tardive dyskinesia in rats (Samad and Haleem, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact pathophysiology of how this drug induces these side effects is not totally clear (Perera et al, 2011). Oxidative stress constitutes a potential pathogenic mechanism that may contribute to movement disturbances, especially to tardive dyskinesia (Perera et al, 2011; Wu et al, 2014; Samad and Haleem, 2017). Recent studies have shown that the repeated administration of haloperidol is able to induce tardive dyskinesia in rats (Samad and Haleem, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress constitutes a potential pathogenic mechanism that may contribute to movement disturbances, especially to tardive dyskinesia (Perera et al, 2011; Wu et al, 2014; Samad and Haleem, 2017). Recent studies have shown that the repeated administration of haloperidol is able to induce tardive dyskinesia in rats (Samad and Haleem, 2017). Another study using plasma and the enzyme manganese superoxide dismutase (MnSOD) as a biomarker of patients with schizophrenia analyzed the relationship of oxidative stress and tardive dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that treatment of activated microglia with RBE further enhanced the gene expression of the microglial M2 marker IL-10 and reduced the expression of pro-inflammatory M1 markers (TNF-α, IL-1β) . Specific protective properties of RBO were observed in the postsynaptic receptor (D2) antagonist haloperidol-induced Tardive dyskinesia, which has potential implications in the treatment of schizophrenia and motor disorders 76) . Nevertheless, the exact mechanism of the whole RBO s activity in cognitive development remains to be discovered.…”
Section: Neuroprotective Function Of Rbomentioning
confidence: 99%
“…The severe adverse effects due to haloperidol treatment, resulting in DA receptors blockade and neurotoxicity, have been associated to increased ROS production [96,97]. Its metabolite, haloperidol pyridiniumion, is highly toxic and increases oxidative stress inducing plasma membrane damages, explaining, at least in part, the pathogenesis of haloperidol-induced parkinsonism symptoms [98,99].…”
Section: First-generation Antipsychotics (Fgas) and Oxidative Stress: The Strange Case Of Haloperidolmentioning
confidence: 99%